Effect of stink bug populations on the yield, seed quality and agronomic traits of soybeans - Gazzoni, Décio Luiz (Pesquisa Agropecuaria Brasileira, 1998)
During the 1995/96 soybean (Glycine max (L.) Merrill.) season, a field study was conducted, in Londrina, PR, Brazil, to evaluate the effect of three stink bug populations on the yield, seed quality, agronomic traits and seed damage of three commercial varieties of soybean. The treatments consisted of the EMBRAPA-4, EMBRAPA-48 and BR-36 soybean varieties, and the density levels of up to two and up to four stink bugs/m of row, besides a natural stink bug population, without chemical control. Weekly samplings were made by the use of the beat cloth method, with six samples/plot, starting at pod set and extending to soybean maturity. When the population reached the established density levels, stink bugs were controlled by an application of endosulfan at 525 g/ha of a.i. The overall mean of stink bugs population during the observed period was 2.1/m of row, boosting the recommended economic damage level. Results indicated that the studied density levels of stink bugs did not affect the yield or the quality of seeds, nor the agronomic traits of the plants. Statistical differences were observed only for the tested varieties, exception to stink bug damage to the seeds, evaluated by the tetrazolium test, where differences due to stink bug population were detected.